(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article notes that in Kyrgyzstan there is a shortage of resources during peak periods of consumption, while at the same time there is a tendency for the population to constantly increase, as well as the need for electricity in the industries, agriculture, public utilities and services. The scientific community has paid close attention to the problem of developing nonraditional ener-gy sources. Demographic growth affects the size and structure of demand directly and through. According to the authors, the prospects for the development of non-traditional energy sources should be considered taking into account population growth, the development of the real sector of the economy and the service sector. Attracting investments for the development of non-traditional energy sources is the basis for increasing energy production, their development and effective use for the development of national and regional economies and the main issues of ensuring the country’s energy security.